Prenatally detected umbilical cord tumor as a sign of diffuse neonatal hemangiomatosis - Schwickert, Alexander; Seeger, Karl‐Heinz; Rancourt, Rebecca C.; Henrich, Wolfgang (Journal of clinical ultrasound, 2019)
We report a case of a prenatally detected hemangioma of the umbilical cord as an early sign of diffuse neonatal hemangiomatosis (DNH). The newborn was diagnosed with multiple hemangiomas in the liver, intestines, skin, and brain. Prenatal ultrasound findings, neonatal appearance of the hemangiomas, and the associated complications are illustrated. Interdisciplinary investigations as well as operative and systemic treatment approaches proved to be challenging. This case illustrates how prenatal ultrasound with color Doppler facilitates the early diagnosis of DNH and can help through the early referral to specialized centers for appropriate treatment.